2013
DOI: 10.1002/anie.201305669
|View full text |Cite
|
Sign up to set email alerts
|

Generation of HNO and HSNO from Nitrite by Heme‐Iron‐Catalyzed Metabolism with H2S

Abstract: Nitrite has been shown in the past decade to be an important source of nitric oxide that acts as a vasodilator and intrinsic signaling molecule. [1] Numerous studies have proved that nitrite can be reduced in vivo, either non-enzymatically [2a,b] or enzymatically, in reactions catalyzed by xanthine oxidase, [2c] deoxyhaemoglobin, [2d] deoxymyoglobin, [2e] cytochrome c, [2f] or by thiol and metal-center-assisted processes inside the cell. [2g] The mechanism of the last process has recently been studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 37 publications
(2 reference statements)
5
100
0
Order By: Relevance
“…Recently, HSNO has been detected under physiologically relevant conditions through protonation of [SNO] − or treatment of S-nitrosoglutathione with sodium sulde by infrared, 15 N NMR and mass spectroscopy. 2 Additionally, coordinated HSNO has been transiently observed by mass spectroscopy 17 and very recently a crystal structure was obtained of an RSNO coordinated to a copper complex. 18 However, these measurements provided only limited insight into the structure and subsequent reactivity of HSNO.…”
mentioning
confidence: 99%
“…Recently, HSNO has been detected under physiologically relevant conditions through protonation of [SNO] − or treatment of S-nitrosoglutathione with sodium sulde by infrared, 15 N NMR and mass spectroscopy. 2 Additionally, coordinated HSNO has been transiently observed by mass spectroscopy 17 and very recently a crystal structure was obtained of an RSNO coordinated to a copper complex. 18 However, these measurements provided only limited insight into the structure and subsequent reactivity of HSNO.…”
mentioning
confidence: 99%
“…The spontaneity of the reaction would depend on pH; at a very low gastric pH, it would not be favored, but it would occur at neutral pH. Further, Filipovic et al have recently demonstrated that HNO and a metal center of an Fe porphyrin can eventually S -nitrosate proteins via H 2 S-assisted mechanism [102]. The same has been shown with Mn(II) cyclic polyamine-based SOD mimic [139].…”
Section: Discussionmentioning
confidence: 99%
“…Our work on rat kidney I/R injury demonstrated that MnTnHex-2-PyP 5+ (as a part of mixture containing growth factors and amino acids of Krebs cycle) upregulates a number of endogenous anti-oxidant enzymes — including mitochondrial and extracellular SOD, GPx, lactoperoxidase, inducible nitric oxide synthase (iNOS), and thioredoxin reductase 1—and a set of peroxiredoxins—heat shock protein 70 (HSP-70) and phospho-heat shock factor 1 (pHSF-1) [42]. Importantly, this study clearly showed that MnP had not acted as an SOD mimic, but perhaps as a pro-oxidant inducing adaptive responses such as activating Nrf2 via oxidation of Keap1, in a manner similar to Mn(II) cyclic polyamine [102,103]. Such mode of action is further substantiated with data from Tome’s group indicating that MnTE-2-PyP 5+ can S -glutathionylate other thiol-bearing proteins, such as complexes I, III, and IV of mitochondrial electron transport chain [99,100].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Later systematic high-level ab inito investigations focused on thionitrous acid HSNO, [25][26][27][28][29][30] the smallest RSNO model molecule that, due to its small size, could be feasibly investigated with the state-of-the-art electronic structure methods. Although HSNO has been recently proposed to be an important biological RSNO in its own right, [31][32][33] accurate high-level computational-and also recently reported 30 experimental-data on HSNO may have only limited utility for understanding the chemistry of the most biologically abundant cysteine-based RSNOs, because the nature of substituent R may significantly affect the properties of the -SNO group. 19,34 The smallest aliphatic RSNO, methyl thionitrite CH 3 SNO, is a far better model of S-nitrosated cysteine sidechain, a primary aliphatic RSNO.…”
Section: Introductionmentioning
confidence: 99%